2008
DOI: 10.1002/cbic.200700560
|View full text |Cite
|
Sign up to set email alerts
|

Linear Analogues of Human β‐Defensin 3: Concepts for Design of Antimicrobial Peptides with Reduced Cytotoxicity to Mammalian Cells

Abstract: A series of engineered linear analogues [coded as F6, W6, Y6, A6, S6 and C(Acm)6] were modeled, designed, synthesized and structurally characterized by mass spectra, circular dichroism, hydrophobicity analysis and molecular modeling. We have screened antimicrobial activity, hemolysis to rabbit erythrocytes, and cytotoxicity to human conjunctival epithelial cells. No significant hemolytic effect was observed for hBD3 or from five of the six analogues [F6, Y6, A6, S6 and C(Acm)6] over the range of 3-100 microg m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
70
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(76 citation statements)
references
References 70 publications
6
70
0
Order By: Relevance
“…Similar conformational changes have been reported for hBD-3 and GCP-2/CXCL6 in membranemimicking conditions (14,15,44). It has been suggested that these structural modifications are involved in the mode of action of antimicrobial proteins (14,15).…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Similar conformational changes have been reported for hBD-3 and GCP-2/CXCL6 in membranemimicking conditions (14,15,44). It has been suggested that these structural modifications are involved in the mode of action of antimicrobial proteins (14,15).…”
Section: Discussionsupporting
confidence: 76%
“…Several antimicrobial peptides and antimicrobial chemokines retain activity as linearized molecules despite the loss of their characteristic ␤-sheet structures (14,15). This questions the requirement of the three-dimensional patch of antimicro- bial chemokines and shows that other structural elements can also be sufficient for antimicrobial activity of these proteins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…B2088 and the monomer peptide were incubated with a human conjunctiva epithelial cell line (IOBA-NHC) as described previously (31,32). The luminescent signal was read by a microplate reader (Tecan GeniosPro, Tecan Asia, Singapore).…”
Section: Methodsmentioning
confidence: 99%
“…Several reports have indicated a correlation between hydrophobicity of AMPs and cytotoxicity (31)(32)(33). Consistent with the proposed hydrophobicity-cytotoxicity relationship, more hydrophobic analogous peptides of hBD3 exhibit greater cytotoxic activity (10,34,35). With respect to the structural aspect, the solution structure of hBD3 is characterized by an amphipathic dimeric structure, which is different from those of hBD1 and hBD2 (36).…”
Section: Discussionmentioning
confidence: 60%